2008
DOI: 10.1108/01409170810846849
|View full text |Cite
|
Sign up to set email alerts
|

Private label competition: the perspective of Swedish branded goods manufacturers

Abstract: Purpose -This paper aims to gain a better understanding of how Swedish branded goods manufacturers (BGMs) deal with the increased usage of private labels. Design/methodology/approach -The approach takes the form of answering the three research questions of this study: how private labels are viewed by BGMs on the Swedish market; how Swedish BGMs strategically respond to the increases in private labels; and how the benefits and drawbacks of these strategic responses are perceived by Swedish BGMs. A contrasting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Eataly is concerned that developing private label products will create tension between themselves and the small branded manufacturers they aim to preserve. The literature recognizes that private labels represent damage to competition among manufacturers' brands (Hultman et al, 2008). Furthermore, Eataly sees private labels as making producers anonymous, in line with those authors that speak about ''theft of identity'' (Davies, 1998).…”
Section: Discussion-innovations In Eataly's Business Modelmentioning
confidence: 95%
“…Eataly is concerned that developing private label products will create tension between themselves and the small branded manufacturers they aim to preserve. The literature recognizes that private labels represent damage to competition among manufacturers' brands (Hultman et al, 2008). Furthermore, Eataly sees private labels as making producers anonymous, in line with those authors that speak about ''theft of identity'' (Davies, 1998).…”
Section: Discussion-innovations In Eataly's Business Modelmentioning
confidence: 95%
“…Gomez and Rubio, 2008), some have dwelt on competition and brand image issues relating to the two types of brands (e.g. Cotterill et al, 2000; Hultman et al, 2008; Mills, 1999; Miranda and Joshi, 2003; Nenycz-Thiel and Romaniuk, 2011; Verhoef et al, 2002; Wu et al, 2011), and yet other research has investigated retailer brands and manufacturer brands from a historical perspective (e.g. Herstein and Gamliel, 2004; Steiner, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Product branding and product price have been studied and found to be important and statistically significant to consumers in terms of quality perception. There has been a recent study on the perceived difference of quality by consumers in the retail area of clothing (Amrouche & Zaccour, 2009;Vahie & Paswan, 2006) and regional perceptions (Cheng, Chen, Lin & Wang, 2007;Hultman, Opoku, Salehi-Sangari, Oghazi & Bui, 2008). In theoretical studies of automotive platform sharing, it was found that the consumers benefit from vertical platform sharing (Ghosh & Morita, 2008).…”
Section: Quality Perception Of Product Brandingmentioning
confidence: 99%